Fabrication and Characterization of Porous Silicon for Photonic Applications - Mabilangan, Arvin I.; Saplagio, Niel Gabriel E.; Anguluan, Eloise P.; Cabello, Neil Irvin F.; Gonzales, Rhona Olivia M.; Somintac, Armando S.; Salvador, Arnel A. (Science Diliman: A Journal of Pure and Applied Sciences, 2013)
Porous silicon (PSi) thin films from p-type silicon (100) substrates were fabricated using a simple table top electrochemical etching setup with a 1:1 HF:EtOh electrolyte solution. Porous silicon f ilms with different morphologies and optical properties were achieved by varying the etching parameters, such as HF concentration, etching time and anodization current. It was observed that the f ilm thickness of the fabricated PSi increased with etch time and HF concentration. The etch rate increased with the applied anodization current. Reflection spectroscopy at normal incidence was used to determine the refractive indices of the fabricated f ilms. Using the Sellmeier equation, the chromatic dispersion of the films was obtained for different HF concentrations and anodization currents. Keywords: Silicon, anodization, porous materials, photonic applications